2016
DOI: 10.1007/s10021-016-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grazing Intensity and Seasons on Greenhouse Gas Emissions in Tropical Grassland

Abstract: Greenhouse gases (GHG) can be affected by grazing intensity, soil, and climate variables. This study aimed at assessing GHG emissions from a tropical pasture of Brazil to evaluate (i) how the grazing intensity affects the magnitude of GHG emissions; (ii) how season influences GHG production and consumption; and (iii) what are the key driving variables associated with GHG emissions. We measured under field conditions, during two years in a palisade-grass pasture managed with 3 grazing intensities: heavy ( 15cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
2
26
1
2
Order By: Relevance
“…Grazing intensity effects CO 2 and N 2 O emissions [12]. Both GHG emissions declined in this study as the grazing intensity decreased.…”
Section: Greenhouse Gasesmentioning
confidence: 51%
See 4 more Smart Citations
“…Grazing intensity effects CO 2 and N 2 O emissions [12]. Both GHG emissions declined in this study as the grazing intensity decreased.…”
Section: Greenhouse Gasesmentioning
confidence: 51%
“…It has been reported that Brachiaria pastures are not a source of CH 4 . These previous studies suggested that the well-drained conditions of this soil favored CH 4 oxidation, which consequently offset the CH 4 production [12].…”
Section: Greenhouse Gasesmentioning
confidence: 70%
See 3 more Smart Citations